Beliefs and practices regarding solid food introduction among Latino parents in Northern California. (1st January 2018) - Beck, Amy L.; Hoeft, Kristin S.; Takayama, John I.; Barker, Judith C.
Abstract : Latino children are more likely to be obese than non-Hispanic white children, and feeding patterns that begin in infancy may contribute to this disparity. The objective of this study was to elucidate beliefs and practices related to the introduction of solids and solid food feeding in the first year of life among low-income Latino parents residing in Northern California. We conducted 26 semi-structured interviews that explored the timing of introduction of solids, selection of foods to serve to infants, feeding strategies, sources of information on solid food feeding and concerns about infant weight. We found that most parents relied on traditional practices in selecting first foods for infants and had a strong preference for homemade food, which was often chicken soup with vegetables. Parents generally described responsive feeding practices; however a minority used pressuring practices to encourage infants to eat more. Very few parents practiced repeated gentle introduction of unfamiliar food to increase acceptance. High calorie low nutrient foods were typically introduced at around 12 months of age and parents struggled to limit such foods once children were old enough to ask for them. Parents were concerned about the possibility of infants becoming overweight and considered health care providers to be an important source of information on infant weight status. The results of this study can be used to inform the development of interventions to prevent obesity in Latino children with similar demographics to our study population.